2022
DOI: 10.1016/j.cub.2021.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Lateral hypothalamic neuronal ensembles regulate pre-sleep nest-building behavior

Abstract: Highlights d Prior to falling asleep, mice mainly engage in nesting and grooming d The capacity to nest prior to sleep promotes sleep initiation and consolidation d Lateral hypothalamus glutamatergic ensembles regulate the motivation to engage in pre-sleep nesting d Lateral hypothalamus glutamatergic ensembles gate sleep initiation and intensity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 80 publications
(127 reference statements)
3
21
0
Order By: Relevance
“…Starting from an unbiased whole-brain survey of activity patterns elicited in different contexts, we associate a group of midbrain neurons, the EWcp CART+ , with maternal behavior. Of note, nesting is most often performed as the first step of a behavioral sequence that leads the animal to sleep ( Eban-Rothschild et al., 2016 ; Sotelo, 2022 ). Our data suggest that the activity of the EWcp CART+ neurons acutely influences the transition to nesting in the wake-to-sleep sequence, and their inhibition is detrimental to the duration of the nesting phase in the sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from an unbiased whole-brain survey of activity patterns elicited in different contexts, we associate a group of midbrain neurons, the EWcp CART+ , with maternal behavior. Of note, nesting is most often performed as the first step of a behavioral sequence that leads the animal to sleep ( Eban-Rothschild et al., 2016 ; Sotelo, 2022 ). Our data suggest that the activity of the EWcp CART+ neurons acutely influences the transition to nesting in the wake-to-sleep sequence, and their inhibition is detrimental to the duration of the nesting phase in the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory settings, mice reorganize their nest daily: in the dark phase, the nest is disorganized by the normal activities of mice but is rebuilt in the same location at the beginning of the light phase before rest ( Jirkof, 2014 ; Jirkof et al., 2013 ). As a result, nest building happens at the start of a behavioral sequence, which consists of nesting, grooming, and then sleep ( Eban-Rothschild et al., 2016 , 2017 ; Sotelo, 2022 ). We reasoned that preparatory nesting could modify profoundly some of the essential behaviors in the daily routine of pregnant females.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly experience that the pre-sleep period is characterized by a series of motivational drives that can significantly modulate sleep [ 17 , 18 ]. In several animal species, the engagement of pre-sleep behaviors has also been documented in terms of changes in neuronal function and interpreted as an important evolutionary adaptation [ 19 ]. In humans, pre-sleep behaviors are thought to facilitate the transition from wakefulness to sleep by reducing alertness and limiting exposure to environmental, activating stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, alterations in sleep and diurnal rhythms, like those observed with feeding behavior, may provide one explanation for why AUD increases AD risk. Interestingly, a recent study also demonstrated that nest-building increases during proximity to sleep in mice (Sotelo, Tyan et al 2022). Although further studies are needed, these findings suggest that chronic ethanol drinking exacerbates disruptions in metabolism and sleep that are frequently observed in AD.…”
Section: Discussionmentioning
confidence: 97%